2017
DOI: 10.13004/kjnt.2017.13.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Remote Hemorrhage after Burr Hole Drainage of Chronic Subdural Hematoma

Abstract: Chronic subdural hematoma (CSDH) and symptomatic subdural hygroma are common diseases that require neurosurgical management. Burr hole trephination is the most popular surgical treatment for CSDH and subdural hygroma because of a low recurrence rate and low morbidity compared with craniotomy with membranectomy, and twist-drill craniotomy. Many reports suggest that placing a catheter in the subdural space for drainage can further reduce the rate of recurrence; however, complications associated with this type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…of cerebrospinal fluid might cause remote intracranial hemorrhage after burr hole surgery. [7,16] In our institution, we insert a drainage tube into the hematoma cavity through a small dura incision and do not perform intraoperative irrigation to avoid a rapid decrease in the intracranial pressure. e drainage would be gradually initiated after the surgery.…”
mentioning
confidence: 99%
“…of cerebrospinal fluid might cause remote intracranial hemorrhage after burr hole surgery. [7,16] In our institution, we insert a drainage tube into the hematoma cavity through a small dura incision and do not perform intraoperative irrigation to avoid a rapid decrease in the intracranial pressure. e drainage would be gradually initiated after the surgery.…”
mentioning
confidence: 99%
“…The clinical and radiological summaries of all the patients are shown in [ Table 1 ]. [ 3 - 6 , 8 , 9 , 11 - 14 , 19 , 20 ] Of the total 17 patients, 16 (94%) had favorable outcomes, including good recovery (88%) and moderate disability (6%). Twelve cases (70.5%) presented with intracerebral hemorrhage (ICH), and only 2 presented IVH.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that rapid or excessive postoperative drainage should be avoided. [6] To reduce the complication, slow and gradual decompressive drainage of CSDH must be performed carefully.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence in the literature suggest that sudden evacuation of chronic subdural hematoma may lead to growth or development of remote (contralateral) subdural, epidural or intra-cerebral haematomas 13 17 . The possible mechanisms behind this phenomenon include the rapid shift of the cerebral hemisphere following hematoma evacuation, over drainage of the subdural space, and cerebral hyperperfusion syndrome, although the actual pathophysiology behind this process remains unclear 16 20 .…”
Section: Discussionmentioning
confidence: 99%